GAMBARAN REBUSAN DAUN KELOR UNTUK MENURUNKAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS DI SUKOHARJO - Yohanes Wahyu Nugroho; Putri Pertiwi (Akademi Keperawatan Giri Satria Husada Wonogiri, 2020)
Background : Moringa (Moringa oleifera) is a shrub plant that is very easily found in Indonesia. The many benefits of Moringa leaves for health make Moringa leaves called magic leaves. The content of antioxidants such as flavonoids, vitamin A, vitamin E, vitamin C and selenium in moringa leaves can help reduce blood sugar levels in the body.Objective : Obtained real experience and effectiveness of tomato juice diet to reduce blood pressure in patients with hypertension to overcome the problem of high blood pressure.Method : This research is a observational study with a one group pretest-posttest design. The population in this study were patients with type II diabetes mellitus in Sukoharjo Village with a total sample of 7 people selected by purposive sampling.Results : The results showed there was an effect of giving Moringa leaf decoction to decrease blood sugar levels of Diabetes Mellitus sufferers. The results of this study are expected to provide new insights and increase knowledge about the use of herbal medicines in tackling Diabetes Mellitus. Latar Belakang : Kelor (Moringa oleifera) merupakan tanaman perdu yang sangat mudah ditemui di Indonesia.Banyaknya manfaat daun kelor untuk kesehatan menjadikan daun kelor disebut sebagai daun ajaib. Kandungan antioksidan seperti flavanoid, vitamin A, vitamin E, vitamin C dan selenium pada daun kelor dapat membantu menurunkan kadar gula darah dalam tubuh.Tujuan : Tujuan penelitian ini adalah untuk mengetahui pengaruh pemberian rebusan daun kelor terhadap penurunan kadar gula darah paa penderita Diabetes Mellitus.Metode : Penelitian ini bersifat metode observasi dengan rancangan one group pretest-posttest. Populasi pada penelitian ini adalah penderita DM type II di Desa Sukoharjo dengan jumlah sampel 7 orang dipilih secara purposive sampling.Hasil : Hasil penelitian menunjukkan terdapat pengaruh pemberian rebusan daun kelor terhadap penurunan kadar gula darah dengan. Hasil penelitian ini diharapkan dapat memberikan wawasan baru dan menambah ilmu pengetahuan tentang penggunaan obat herbal dalam menanggulangi penyakit Diabetes Mellitus.